Geriatric Psychiatry A Case-Based Textbook (Springer International Publishing, 2018)
This textbook presents real-world cases and discussions that introduce the various mental health syndromes found in the aging population before delving into the core concepts covered by geriatric psychiatry curricula. The text follows each case study with the vital information necessary for physicians in training, including key features of each disorder and its presentation, practical guidelines for diagnosis and treatment, clinical pearls, and other devices that are essential to students of geriatric psychiatry. With the latest DSM-5 guidelines and with rich learning tools that include key points, review questions, tables, and illustrations, this text is the only resource that is specifically designed to train both American and Canadian candidates for specialty and subspecialty certification or recertification in geriatric psychiatry. It will also appeal to audiences worldwide as a state-of-the-art resource for credentialing and/or practice guidance . The text meets the needs of the future head on with its straightforward coverage of the most frequently encountered challenges, including neuropsychiatric syndromes, psychopharmacology, eldercare and the law, substance misuse, mental health following a physical condition, medical psychiatry, and palliative care. Written by experts in the field, Geriatric Psychiatry: A Case-Based Textbook is the ultimate resource for graduate and undergraduate medical students and certificate candidates providing mental health care for aging adults, including psychiatrists, psychologists, geriatricians, primary care and family practice doctors, neurologists, social workers, nurses, and others.